Intellectual Property - Synthesis of Intellect, Economics and Law - Y. D. Yakovsky (Наука и техника)
The paper considers practical aspects in the field of creation, legal protection and commercialization of intellectual activity. Classification and description of the objects of intellectual property are given in the paper. The paper contains the analysis of types of safeguard documents and terms of validity of exclusive rights to copyrights and industrial property.